2014
DOI: 10.1523/jneurosci.3074-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Is Produced by a Specific Subset of Taste Receptor Cells and Critical for Maintaining Structural Integrity of Mouse Taste Buds

Abstract: Although inflammatory responses are a critical component in defense against pathogens, too much inflammation is harmful. Mechanisms have evolved to regulate inflammation, including modulation by the anti-inflammatory cytokine interleukin-10 (IL-10). Previously we have shown that taste buds express various molecules involved in innate immune responses, including the proinflammatory cytokine tumor necrosis factor (TNF). Here, using a reporter mouse strain, we show that taste cells also express the anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 59 publications
4
43
0
1
Order By: Relevance
“…Our studies have found that several inflammation-associated cytokines are preferentially expressed in taste bud cells compared to nontaste lingual epithelial cells (Cohn et al, 2010; Feng et al, 2014a; Feng et al, 2014b; Feng et al, 2012; Kim et al, 2012; Wang et al, 2007), suggesting that these cytokines may have special functions in the peripheral taste system. In particular, we have found that TNF is specifically expressed in a subset of taste bud cells even in healthy mice (Feng et al, 2012; Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our studies have found that several inflammation-associated cytokines are preferentially expressed in taste bud cells compared to nontaste lingual epithelial cells (Cohn et al, 2010; Feng et al, 2014a; Feng et al, 2014b; Feng et al, 2012; Kim et al, 2012; Wang et al, 2007), suggesting that these cytokines may have special functions in the peripheral taste system. In particular, we have found that TNF is specifically expressed in a subset of taste bud cells even in healthy mice (Feng et al, 2012; Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 60%
“…Interferon-γ is expressed in a subset of type II and III taste cells (Kim et al, 2012). The anti-inflammatory cytokine IL-10 is expressed in type II bitter cells (Feng et al, 2014a). Whether these cytokines are involved in taste sensing remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, glial cell line-derived neurotrophic factor is expressed in a different subset of taste bud cells than BDNF (Suzuki et al, 2007; Takeda et al, 2004), and its receptors are expressed in the geniculate ganglion (Farbman et al, 2004b; Yamout et al, 2005). However, many other factors could also play this role/s (Feng et al, 2014; Germana et al, 2006; McLaughlin, 2000; Suzuki et al, 2007; Suzuki et al, 2005; Takeda et al, 2005; Yee et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Notably, inflammation appears to play a role in many of the conditions and diseases associated with taste impairments (Zhu et al , ; Kumarhia et al , ). These studies suggest that immune responses may play a role for maintaining structural integrity of taste buds (Kim et al , ; Feng et al , ); however, little information has been generated regarding inflammation–taste interactions.…”
Section: Introductionmentioning
confidence: 99%